A-Ring Synthons of 19-Nor Type Vitamin D Derivatives. Issue 173 (October 2017) - Akagi, Yusuke; Yasui, Koji; Nagasawa, Kazuo
Graphical abstract: Abstract: Various 19-nor vitamin D analogs, which lack the methylene group at C19, exhibit significant vitamin D (VD)-related biological activities, but generally show a reduced calcemic side-effect compared with VD itself. Among them, paricalcitol is already used clinically for treatment and prevention of secondary hyperparathyroidism associated with chronic renal failure. Therefore, considerable synthetic efforts have been directed towards 19-nor VD analogs, focusing especially on A-ring synthons suitable for use in convergent synthetic strategies based on coupling of CD-ring synthons and A-ring synthons. For example, we have recently developed a new synthetic route to A-ring synthons from linear dienes based upon a ring-closing olefin metathesis strategy. Here, we review recent synthetic approaches to A-ring synthons for 19-nor VD derivatives.